The Ever-Evolving Brand of the Land-Grant Institution: A Historical Overview - Audrey E. H. King; M. Craig Edwards (Journal of Applied Communications, 2021)
A brand is a multifaceted system of management choices and consumer responses that distinguishes products, goods, services, or ideas and creates awareness and meaning. In a highly competitive environment, the importance of the branding of universities is continually increasing. Land-Grant Institutions (LGIs) have a long and storied history of serving the public, who may have little awareness of the institutions’ overall missions or importance. This inquiry sought to describe the brand and branding of LGIs over time. The Morrill Act of 1862 established LGIs and their brand as schools of higher learning for the common people. The LGI and its brand was expanded through the Hatch Act of 1887 and Smith-Lever Act of 1914. LGIs have undergone many changes, some of which are name changes. The total number of name changes for all 1862 LGIs is 93. Even though the overall brand of LGIs as a system has changed, adapted, evolved, and rebranded numerous times, the original brand mission and vision have remained intact. Results suggest most LGIs have renamed or rebranded to be more appealing to broader audiences and to populations not directly tied to the agricultural sector and rural America.
Keywords: Branding; land-grant institutions; land-grant mission; rebrand